Determination Kinetic Parameters of Endo-β-1,4-D-Xylanase from Abdomenal Termites with Xylan Oat and Birchwood - Istri Ratnadewi, Anak Agung; Linda Faiqotul Himmah; Tri Mulyono; Wuryanti Handayani; NG. Krishnabudi; Sudarko (Indonesian Chimica Letters, 2022)
Parameters kinetic (KM, VMax, and kCat) endo-β-1,4-D-xylanase under optimum conditions with oat spelt xylan and birchwood substrate have been investigated in this study. Hydrolysis of endo-β-1,4-D-xylanase using variation of substrate concentration (b/v) ranging from 0.2 to 1.2%. Variation of incubation time is up to 20 hours with 4 hours interval at the optimum temperature of the enzyme, 40°C. The results obtained from this study were the KM of endo-β-1,4-D-xylanase for oat spelt xylan and birchwood were 4.10 mg/ml and 0.681 mg/ml, respectively. VMax values, and kCat for oat spelt xylan substrate of 0.28 mg/ml.jam and 1.7 x 10-3 s-1. While VMax, and kCat for birchwood substrate that is 0.117 mg/U/jam and 7 x 10-4 s-1. From the results of this study we found that endo-β-1,4-D-xylanase can hydrolaze substrates which have differences solubility.